Hybrid Learning In English Subject : A Case Study At Widyakarya Catholic University Of Malang - Andy Endra Krisna (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Learning models develop as technology develops. Nowadays teachers can no longer teach using conventional teaching methods only but they also have to use technology for teaching. The use of technology in teaching does not mean that you have to abandon old methods. However, combining the two could be a good alternative. One of the learning models is the hybrid learning or blended learning model. What is its application in teaching English courses at the Catholic University of Widya Karya Malang? This research explores the process of using hybrid learning in learning English at Widya Karya Catholic University Malang, especially in English subject . The method used in this research is a qualitative descriptive method, which provides an overview of the implementation of this learning method. It turns out that using this method provides many positive benefits both from the teacher's side and from the student's side.